2020
DOI: 10.1093/mnras/staa3203
|View full text |Cite
|
Sign up to set email alerts
|

The changing circumgalactic medium over the last 10 Gyr – I. Physical and dynamical properties

Abstract: We present an analysis of the physical and dynamical states of two sets of EAGLE zoom simulations of galaxy haloes, one at high redshift (z = 2 − 3) and the other at low redshift (z = 0), with masses of ≈1012 M⊙. Our focus is how the circumgalactic medium (CGM) of these L* star-forming galaxies change over the last 10 Gyr. We find that the high-z CGM is almost equally divided between the “cool” (T < 105 K) and “hot” (T ≥ 105 K) phases, while at low-z the hot CGM phase contains 5 × more mass than the coo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 83 publications
(110 reference statements)
1
8
0
Order By: Relevance
“…(iv) The line-of-sight velocities of H absorption found near the major axis of a galaxy show a significant tendency to align with the galaxy rotation, suggesting a strong coupling between the angular momentum of the CGM and galaxy (as found by e.g. DeFelippis et al 2020;Huscher et al 2021).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…(iv) The line-of-sight velocities of H absorption found near the major axis of a galaxy show a significant tendency to align with the galaxy rotation, suggesting a strong coupling between the angular momentum of the CGM and galaxy (as found by e.g. DeFelippis et al 2020;Huscher et al 2021).…”
Section: Discussionmentioning
confidence: 86%
“…We attempt to determine whether the major-axis population discussed above is indeed the same co-rotating material identified in Mg (e.g Zabl et al 2019), as well as found in simulations (e.g Huscher et al 2021;DeFelippis et al 2020). We compare the velocity offsets between galaxies and H absorbers found near to their major axes with the stellar rotation of the galaxies determined from emission lines in the MUSE data.…”
Section: Kinematicsmentioning
confidence: 84%
See 1 more Smart Citation
“…Rich and complex kinematic structures of circumgalactic gas around galaxies have already been seen in cosmological simulations (Nelson et al 2013;Ford et al 2014;Anglés-Alcázar et al 2017;Oppenheimer 2018;Hafen et al 2019;Nelson et al 2020), such as extended, warped and thick disks due to cosmological gas accretion (Stewart et al 2011b(Stewart et al , 2013, gas associated with accreting satellites (Shao et al 2018) and stream accretion from the cosmic web (Dekel et al 2009;Danovich et al 2015) etc. In particular, high-angularmomentum co-rotating (with respect to stellar disks) circumgalactic gas associated with simulated galaxies is found to extend to ∼ 100 kpc (El-Badry et al 2018;Ho et al 2020;Huscher et al 2021;DeFelippis et al 2021).…”
Section: Introductionmentioning
confidence: 89%
“…The gradient is of an order two times the estimated one-dimensional velocity dispersion of the dark matter halo. Rotating disc of ∼100 kpc size is not expected to be in place by 𝑧 ∼ 2 (e.g., DeFelippis et al 2020;Huscher et al 2021). Together with the filamentary morphology, the northern and southern edges are most consistent with tracing inflowing streams.…”
Section: Spatially Resolved Kinematicsmentioning
confidence: 99%